Small Bowel Obstruction Caused by Internal Hernia through a Peritoneal Defect of the Pouch of Douglas: Report of a Case and Review of the Literature - Pyong Wha Choi (Case Reports in Surgery)
Herniation of small bowel through the peritoneal defect of the Pouch of Douglas is extremely rare type of internal hernia, and this type of internal hernia has been described as an entity of perineal hernia. Here, we describe a case of a 26-year-old female without history of abdominal surgery presenting with incarcerated small bowel hernia through a peritoneal defect of the Pouch of Douglas. She visited an emergency department presenting with abdominal pain and distension. Without improvement symptom by conservative management, an operation was performed. During the operation, the distal ileum had been herniated through a peritoneal defect of the Pouch of Douglas, and there were no specific findings on gynecological examination. Reduction of the herniated bowel and primary repair of the peritoneal defect were performed. The case represents a very rare type of internal hernia and provides published cases of hernia through a peritoneal defect of the Pouch of Douglas.